RETRACTED: Klasifikasi Data Time Series Arus Lalu Lintas Jangka Pendek Menggunakan Algoritma Adaboost dengan Random Forest - Ahmad Rofiqul Muslikh; Heru Agus Santoso; Aris Marjuni (Universitas Nahdlatul Ulama Blitar, 2019)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in BRILIANT: Jurnal Riset dan Konseptual to article entitled Klasifikasi Data Time Series Arus Lalu Lintas Jangka Pendek Menggunakan Algoritma Adaboost Dengan Random Forest Vol 4, No 1, pp. 78-96, February 2019, DOI: http://dx.doi.org/10.28926/briliant.v3i3.272.This article has been found to be in violation of the BRILIANT: Jurnal Riset dan Konseptual Publication principles and has been retracted.The editor investigated and found that the article published in Jurnal Teknologi Informasi CyberKU Vol. 14 no 1 January 2018, pp. 24-38.The document and its content has been removed from BRILIANT: Jurnal Riset dan Konseptual, and reasonable effort should be made to remove all references to this article.